Evaluasi Penilaian Proses Menggunakan Model Alkin pada Mata Pelajaran Fisika SMAN Se-Gorontalo - Fira Lakoro; Masri Kuadrat Umar; Dewa Gede Eka Setiawan (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
This study was conducted to know the level activity of physics teachers in making preparations, planning, implementation until reporting learning outcomes in one year. This study aims to determine the evaluation process in physics subjects in State Junior High Schol throughout Gorontalo Province with the Alkin model approach. The method used in research was quantitative method. The results of the study were obtained based on questionnaire that containing questions regarding the evaluation of the assessment process carried out by physics teachers in Gorontalo Province. The results showed that the evaluation process of assessment in Gorontalo Province was included in the very good category or above 81%.